Concentrations and Uptake of Dissolved Organic Phosphorus Compounds in the Baltic Sea - Nausch, Monika; Achterberg, Eric P.; Bach, Lennart T.; Brussaard, Corinna P. D.; Crawfurd, Katharine J.; Fabian, Jenny; Riebesell, Ulf; Stuhr, Annegret; Unger, Juliane; Wannicke, Nicola (Frontiers in Marine Science, 2018)
The dissolved organic phosphorus (DOP) pool in marine waters contains a variety of different compounds. Knowledge of the distribution and utilization of DOP by phyto- and bacterioplankton is limited but critical to our understanding of the marine phosphorus cycle. In the Baltic Sea, detailed information about the composition of DOP and its turnover is lacking. This study reports the concentrations and uptake rates of DOP compounds, namely, adenosine triphosphate (dATP), deoxyribonucleic acid (dDNA), and phospholipids (dPL), in the Baltic Proper and in Finnish coastal waters in the summers of 2011 and 2012. The mean concentrations of dATP-P, dDNA-P and dPL-P were 4.3-6.4 nM, 0.05-0.12 nM and 1.9-6.8 nM, respectively, together contributing between 2.4 and 5.2% of the total DOP concentration. The concentrations of the compounds varied between and within the investigated regions and behaved independently. dATP-P and dDNA-P were consumed simultaneously with dissolved inorganic phosphorus (DIP) at rates of 6.9-24.1 nM d-1 and 0.09-0.19 nM d-1, respectively. Thus, these DOP compounds complemented the P supply to microorganisms by 17-36%. Our results indicate that the investigated DOP compounds, particularly dATP-P, can make significant contributions to the P nutrition of microorganisms and show independent dynamics. Therefore, detailed knowledge of all DOP components and their development is required to understand the roles of DOP in marine ecosystems.